Vance Randolph book typescripts - Randolph, Vance, 1892-1980.; Randolph, Vance, 1892-1980.; Randolph, Vance, 1892-1980.; Randolph, Vance, 1892-1980.; Randolph, Vance, 1892-1980.; Wilson, George P. (George Pickett), 1888-1972.
Typescripts, with corrections in ink, of four of Randolph's books: Ozark Superstitions (1947); We Always Lie to Strangers: Tall Tales from the Ozarks (1951); Who Blowed Up the Church House? and Other Ozark Folk Tales (1952); and Down in the Holler: A Gallery of Ozark Folk Speech (1953) which was written with George P. Wilson.
Typescripts.
Library of Congress American Folklife Center.
Author and folklorist.
Collection material in English.
Keywords: Folklore -- Arkansas; Folklore -- Missouri; Folklore -- Oklahoma; Folklore -- Ozark Mountains; Arkansas -- Social life and customs; Missouri -- Social life and customs; Oklahoma -- Social life and customs; Ozark Mountains -- Social life and customs; Authors; Folklorists